Formulation of Body Odor Bacteria Inhibiting Deodorant Spray from Ethyl Acetate Extract of Klika Kesambi - Jalil Genisa, Nur Khairi; Ismail; Maulita Indrisari; Andi Nur Aisyah, Andi Nur Aisyah; Syamsu Nur, Syamsu Nur (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2024)
Acne is one of the skin damages caused by acne-causing bacteria. Flavonoids, saponins, and tannins in taro tubers can potentially have activity against acne-causing bacteria. This study aims to determine the formulation of extract transparent solid soap preparation that meets the characteristics and assess the activity of soap preparation as anti-acne against acne-causing bacteria. Taro tubers were extracted by maceration method. The extract was formulated as transparent solid soap preparations with variations in extract concentration, namely F0 0%, F1 2%, F2 4%, and F3 8%. The soap was evaluated for characteristics including organoleptic test, pH, moisture content, free fatty acids and alkali, mineral oil test, and foam stability test. Antibacterial activity testing of transparent soap extracts was carried out against acne-causing bacteria. The extraction results obtained an extract yield of 10.86%, the three extract formulas have transparent solid soap characteristics that meet the requirements. Soap preparation formula 1 has an inhibition zone of 21.66 ± 0.31 mm against P. acnes bacteria, 19.11±0.53 mm against S. epidermidis, 21.74±0.34 mm against S. aureus. Soap preparation formula 2 has an inhibition zone of 18.53±0.26 mm against P. acnes bacteria, 18.71±0.49 mm against S. epidermidis, 20.16±0.34 mm against S.aureus and soap preparation formula 3 has an inhibition zone of 19.03±0.68 mm against P. acnes bacteria, 19.93±0.86 mm against S. epidermidis, 22.75±0.59 mm against S.aureus. In conclusion, formula 2 with 2% extract concentration has the best soap characteristics and has the most optimal inhibition zone.